Gravity Wave Influences On Mesoscale Divergence: An Observational Case Study. Issue 1 (17th January 2020) - Stephan, C. C.; Lane, T. P.; Jakob, C.
Abstract: Characteristics of tropospheric low‐frequency gravity waves are diagnosed in radiosonde soundings from the Tropical Warm Pool‐International Cloud Experiment near Darwin, Australia. The waves have typical vertical wavelengths of about 4 km, horizontal wavelengths of about 600 km, and intrinsic periods of about 12 hr. These scales match those of the vertical, horizontal, and temporal variability found in area‐averaged horizontal wind divergence over the same domain. Vertical profiles of divergence show wave‐like structures with variability of the order of 2  ×  10 − 5  s − 1 in the free troposphere. The results for Darwin are similar to previously reported observed mesoscale patterns of divergence/convergence over the tropical Atlantic. The findings imply that tropical divergence on spatial scales of a few hundred kilometers, which is known to influence the organization of convection, may be forced by gravity waves. Plain Language Summary: On horizontal scales of several tens to hundreds of kilometers, which we call "mesoscale, " mean vertical motion is very small compared to mean horizontal motion. Yet the vertical motion exerts a critical influence on the formation of clouds: Large‐scale descent is associated with fair weather, and ascent is associated with cloudiness. Weather and climate modeling often assumes that mesoscale vertical motion varies slowly in the three spatial dimensions and with time. Recent observations over the tropical Atlantic, however, showed strong variability in mesoscale vertical motion, implying that clouds do not only respond to vertical motion but may themselves trigger vertical motion in their vicinity. This study reports similar variability also near Darwin, Australia. One way in which clouds can trigger remote vertical motion is by emitting waves, similar to stones that are thrown into a pond. This study examines vertical profiles of horizontal wind speed that were measured by instruments on ascending balloons near Darwin, Australia. These observations do indeed show waves that can provide a plausible explanation for the patterns of noteworthy variability in mesoscale motions. These findings suggest a two‐way coupling of clouds to their environment with potentially important consequences for our understanding of weather and climate phenomena. Key Points: Mesoscale divergence profiles near Darwin show similar long‐lived fine‐scale vertical structure to that reported over the tropical Atlantic High‐resolution soundings are used to test if gravity waves can serve as a plausible explanation for the observed divergence variability Results imply that spatial and temporal variability of mesoscale horizontal divergence are consistent with a forcing by gravity waves